Overlapping vitamin A interventions with provitamin A carotenoids and preformed vitamin A cause excessive liver retinol stores in male Mongolian gerbils - Sowa, Margaret; Mourao, Luciana; Sheftel, Jesse; Kaeppler, Mikayla; Simons, Gabrielle (American Society for Nutrition, 2020)
Background: Vitamin A (VA) deficiency is a public health problem in some countries. Fortification, supplementation, and increased provitamin A consumption through biofortification are efficacious, but monitoring is needed due to risk of excessive VA intake when interventions overlap. Objectives: Two studies in 28–36-d-old male Mongolian gerbils simulated exposure to multiple VA interventions to determine the effects of provitamin A carotenoid consumption from biofortified maize and carrots and preformed VA fortificant on status. Methods: Study 1 was a 2 × 2 × 2 factorial design (n = 85) with high-β-carotene maize, orange carrots, and VA fortification at 50% estimated gerbil needs, compared with white maize and white carrot controls. Study 2 was a 2 × 3 factorial design (n = 66) evaluating orange carrot and VA consumption through fortification at 100% and 200% estimated needs. Both studies utilized 2-wk VA depletion, baseline evaluation, 9-wk treatments, and liver VA stores by HPLC. Intestinal scavenger receptor class B member 1 (Scarb1), β-carotene 15,15′-dioxygenase (Bco1), β-carotene 9′,10′-oxygenase (Bco2), intestine-specific homeobox (Isx), and cytochrome P450 26A1 isoform α1 (Cyp26a1) expression was analyzed by qRT-PCR in study 2. Results: In study 1, liver VA concentrations were significantly higher in orange carrot (0.69 ± 0.12 μmol/g) and orange maize groups (0.52 ± 0.21 μmol/g) compared with baseline (0.23 ± 0.069 μmol/g) and controls. Liver VA concentrations from VA fortificant alone (0.11 ± 0.053 μmol/g) did not differ from negative control. In study 2, orange carrot significantly enhanced liver VA concentrations (0.85 ± 0.24 μmol/g) relative to baseline (0.43 ± 0.14 μmol/g), but VA fortificant alone (0.42 ± 0.21 μmol/g) did not. Intestinal Scarb1 and Bco1 were negatively correlated with increasing liver VA concentrations (P < 0.01, r2 = 0.25–0.27). Serum retinol concentrations did not differ. Conclusions: Biofortified carrots and maize without fortification prevented VA deficiency in gerbils. During adequate provitamin A dietary intake, preformed VA intake resulted in excessive liver stores in gerbils, despite downregulation of carotenoid absorption and cleavage gene expression.